Scoping review: quality of life of siblings of children who are deaf and hard of hearing, have a vision or motor impairment - Veldhorst, Carlijn; Luijmes, Anna; Kef, Sabina; Vervloed, Mathijs P. J.; Steenbergen, Bert (Frontiers in Rehabilitation Sciences, 2023)
This study identified the current state of art about the Quality of Life (QoL) of siblings of children who are deaf and hard of hearing (DHH), have vision impairment (VI) or motor impairment (MI). Additionally, factors associated with individual variation in QoL were examined. A scoping review was performed using PsycInfo, ERIC, Web of Science, and CINAHL. Empirical studies with siblings (age 0-18 years) of children who are DHH, have VI or MI that investigate the QoL of siblings were included. A total of 1746 studies were identified of which 11 met the inclusion criteria. The results showed that QoL has different interpretations and various measurement tools are used. The findings showed both positive and negative outcomes for the QoL of siblings. For example, family cohesion was found as a positive consequence. A negative consequence could be a higher score on problem behavior. Personal and parental characteristics such as age and parental availability were two main factors related to individual variation in QoL. Insight in the factors related to individual variation may help researchers to consider the research perspective. In addition, healthcare providers can use the information to be either aware or intervene on specific factors that are related to the QoL of the children who are DHH, have VI or MI and their siblings.